Study on fracture behavior of individual InAs nanowires using an electron-beam-drilled notch. Issue 27 (15th March 2017) - Choi, Suji; Lee, Jong Hoon; Pin, Min Wook; Jang, Dong Won; Hong, Seong-Gu; Cho, Boklae; Lee, Sang Jun; Jeong, Jong Seok; Yi, Seong-Hoon; Kim, Young Heon
Abstract : The mechanical properties and fracture behavior of individual InAs nanowires (NWs) were investigated under uniaxial tensile loading in a transmission electron microscope. Abstract : The mechanical properties and fracture behavior of individual InAs nanowires (NWs) were investigated under uniaxial tensile loading in a transmission electron microscope. The InAs NWs exhibited elastic deformation during the tensile test till fracture and the experiments revealed a brittle fracture on the (111) plane of a zinc-blende structure. Hemi-ellipse-shaped notches with various radii of curvature, formed via a focused electron beam, were utilized to investigate the fracture behavior when there is a structural flaw at the nanometer scale. The dimensions of notches are controlled with proper understanding of electron beam irradiation on the InAs material system. The stress concentration phenomena with dependence on the notch size are demonstrated in the InAs NWs by analyzing the results from a finite element method simulation.